THE MEDIATING EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT BETWEEN TALENT CULTURE AND EMPLOYEE ENGAGEMENT AMONG EMPLOYEES OF MALAYSIAN GLCs - Isa A.; Ibrahim H.I.; Mohan M.D.; Jaaffar A.H.; Tajudin A.; Khalid N.; Alsheikh G.A.A. (ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2024)
Objective: The aim of this study is to examine how perceived organizational support mediated the relationship between talent culture and employee engagement among employees in the Malaysian governments-linked companies (GLCs). Theoretical framework: The dependent variable for this study is employee engagement while talent culture constitute the independent variable and perceived organizational support is the mediating in this study. Method: The survey distributed received responses from 164 employees currently employed at the 47 GLCs. The study utilised partial least square structural equation modelling (PLS-SEM) method to analyse the data and obtain results for the hypotheses generated. Results and conclusion: The results indicated that none of the mediated relationship were significant. Implications of the research: The findings will be able to provide guidance to the organizations' top management to streamline their operations, business framework and values with the concepts of talent management practices, perceived organization support and employee engagement. Originality/value: In general, this study will be beneficial for GLCs to understand the importance implications of talent management practices in order to attract and retain critical talent and reduce employee turnover in their business entity. 2023 ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao. All rights reserved.